Réponses

Meilleure réponse !
2014-10-02T18:17:01+02:00
Bonjour
fonction affine  f(x) = ax+b
on sait que
f(1/2) = 1  alors  a(1/2) + b = 1 
f(1) = 1/4  alors  a(1) + b = 1/4 
soit le système 
a+b = 1/4                          et                   (1/2)a + b = 1 
b = (1/4 ) - a                     et                    (1/2)a - a + 1/4 = 1 
                                                               ( 1/2)a = -3/4 
                                                                 a = -3/2 
b = (1/4) - (-3/2) = 7/4 

f(x) = (-3/2)x + 7/4